Developmental patterns of extracellular matrix molecules in the embryonic and postnatal mouse hindbrain - Wéber, Ildikó; Dakos, Adél; Mészár, Zoltán; Matesz, Clara; Birinyi, András (Frontiers in Neuroanatomy, 2024)
Normal brain development requires continuous communication between developing neurons and their environment filled by a complex network referred to as extracellular matrix (ECM). The ECM is divided into distinct families of molecules including hyaluronic acid, proteoglycans, glycoproteins such as tenascins, and link proteins. In this study, we characterize the temporal and spatial distribution of the extracellular matrix molecules in the embryonic and postnatal mouse hindbrain by using antibodies and lectin histochemistry. In the embryo, hyaluronan and neurocan were found in high amounts until the time of birth whereas versican and tenascin-R were detected in lower intensities during the whole embryonic period. After birth, both hyaluronic acid and neurocan still produced intense staining in almost all areas of the hindbrain, while tenascin-R labeling showed a continuous increase during postnatal development. The reaction with WFA and aggrecan was revealed first 4th postnatal day (P4) with low staining intensities, while HAPLN was detected two weeks after birth (P14). The perineuronal net appeared first around the facial and vestibular neurons at P4 with hyaluronic acid cytochemistry. One week after birth aggrecan, neurocan, tenascin-R, and WFA were also accumulated around the neurons located in several hindbrain nuclei, but HAPLN1 was detected on the second postnatal week. Our results provide further evidence that many extracellular macromolecules that will be incorporated into the perineuronal net are already expressed at embryonic and early postnatal stages of development to control differentiation, migration, and synaptogenesis of neurons. In late postnatal period, the experience-driven neuronal activity induces formation of perineuronal net to stabilize synaptic connections.